World Bank Group Climate Change Action Plan 2021–2025 : Supporting Green, Resilient, and Inclusive Development - World Bank Group (World Bank, Washington, DC, 2021)
The Climate Change Action Plan 2021–2025 aims to advance the climate change aspects of the WBG’s Green, Resilient, and Inclusive Development (GRID) approach, which pursues poverty eradication and shared prosperity with a sustainability lens. In the Action Plan, we will support countries and private sector clients to maximize the impact of climate finance, aiming for measurable improvements in adaptation and resilience and measurable reductions in GHG emissions. The Action Plan also considers the vital importance of natural capital, biodiversity, and ecosystems services and will increase support for nature-based solutions, given their importance for both mitigation and adaptation. As part of our effort to drive climate action, the WBG has a long-standing record of participating in key partnerships and high-level forums aimed at enhancing global efforts to address climate change. The new Action Plan represents a shift from efforts to “green” projects, to greening entire economies, and from focusing on inputs, to focusing on impacts. It focuses on (i) integrating climate and development; (ii) identifying and prioritizing action on the largest mitigation and adaptation opportunities; and (iii) using those to drive our climate finance and leverage private capital in ways that deliver the most results. That means helping the largest emitters flatten the emissions curve and accelerate the downward trend and ramping up financing on adaptation to help countries and private sector clients prepare for and adapt to climate change while pursuing broader development objectives through the GRID approach.